MANNEQUINS IN MUSEUMS power and resistance on display. - Cooks, Bridget R., 1972-; Wagelie, Jennifer J. ([S.l.] : ROUTLEDGE, 2021)
Mannequins in Museums is a collection of historical and contemporary case studies that examine how mannequins are presented in exhibitions and shows that, as objects used for storytelling, they are not neutral objects. Demonstrating that mannequins have long histories of being used to promote colonialism, consumerism, and racism, the book shows how these histories inform their use. It also engages readers in a conversation about how historical narratives are expressed in museums through mannequins as surrogate forms. Written by a select group of curators and art historians, the volume provides insight into a variety of museum contexts, including art, history, fashion, anthropology and wax. Drawing on exhibition case studies from North America, South Africa, and Europe, each chapter discusses the pedagogical and aesthetic stakes involved in representing racial difference and cultural history through mannequins. As a whole, the book will assist readers to understand the history of mannequins and their contemporary use as culturally relevant objects. Mannequins in Museums will be compelling reading for academics and students in the fields of museum studies, art history, public history, anthropology and visual and cultural studies. It should also be essential reading for museum professionals who are interested in rethinking mannequin display techniques.
Keywords: SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Anthropology / Cultural; Museum manikins; Museums and minorities; Art -- Exhibitions -- Social aspects; Art -- Exhibitions -- Philosophy